Assessing new methods for measuring forest understorey vegetation using terrestrial laser scanning - Ryding, Joseph (2016)
Forest structure is the complex 3D arrangement of all components within the forest architecture. This includes stems, foliage, branches (the components of trees) but also includes non-tree components such as understorey shrubs and herbs. Understanding the structural components of forests is critical when considering forest ecosystems. The structure of a forest can affect functional and compositional characteristics such as productivity and species richness with structure being an important factor influencing animal-habitat associations. Structural characteristics of forests include the size distribution and spatial organisation of trees, and the horizontal and vertical density of objects within the understorey.